Repeatability and reproducibility of right ventricular Tei index valves derived from three echocardiographic methods for evaluation of cardiac function in dogs - Morita, Tomoya; Nakamura, Kensuke; Osuga, Tatsuyuki; Lim, Sue Yee; Yokoyama, Nozomu; Morishita, Keitaro; Ohta, Hiroshi; Takiguchi, Mitsuyoshi (American Veterinary Medical Association, 2016)
Objective: To evaluate repeatability and reproducibility of right ventricular Tei index (RTX) values derived from dual pulsed-wave Doppler, conventional pulsed-wave Doppler, and tissue Doppler echocardiography and to investigate relationships and repeatability among the 3 methods in healthy dogs. Animals: 6 healthy adult Beagles. Procedure: Echocardiography was performed on each dog on different days for 2 weeks (3 times/d) by 2 echocardiographers. Intraobserver within- and between-day and interobserver coefficients of variation (CVs) and intraclass correlation coefficients (ICCs) for RTXs derived from dual pulse-waved Doppler (RTXDPD), conventional pulsed-wave Doppler (RTXPD), and tissue Doppler (RTXTD) methods were determined. Degrees of agreement among RTX values derived from the 3 methods were assessed by modified Bland-Altman analysis. Results: Least squares mean (95% confidence interval) RTXtd was 0.50 (0.46 to 0.54), which was significantly higher than that for RTXDPD (0.27 [0.23 to 0.31]) and RTXPD (0.25 [0.21 to 0.29]). Agreement between RTXDPD and RTXPD was good (bias [mean difference], 0.04 [95% confidence interval, −0.03 to 0.10]). The RTXdpd had high within-day (CV, 6.1; ICC, 0.77) and interobserver (CV, 3.5; ICC, 0.83) repeatability, but between-day repeatability was not high. The RTXtd had high within-day repeatability (CV, 6.0; ICC, 0.80), but between-day and interobserver repeatability were not high. Within-day, between-day, and interobserver repeatability of RTXPD were not high. Conclusions and clinical relevance: RTXdpd measurement was a repeatable and reproducible method of cardiac evaluation in healthy dogs. The RTXTD values were significantly higher than the RTXDPD and RTXPD values; therefore, RTX values derived from different echocardiographic methods should be interpreted with caution.